1950
DOI: 10.1152/ajplegacy.1950.161.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Exchange in Parabiotic Rats

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1952
1952
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Parabiotic rats such as those used in the present experiments have a common circulation and an exchange of blood between rats with a half-time of about 1 hour (17).…”
Section: Discussionmentioning
confidence: 99%
“…Parabiotic rats such as those used in the present experiments have a common circulation and an exchange of blood between rats with a half-time of about 1 hour (17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, with each parabiosis procedure it is essential that blood exchange be established and that the rate of blood exchange between partners is measured. In the early 1900’s there was some disagreement as to whether whole blood could exchange between parabiosed animals, or whether there was a “parabiotic barrier” (see review by Huff et al [38]). Starting with the initial studies by Bert [1] a number of investigators identified common blood vessels in parabiosed pairs of rats and Suaerbruch and Heyde [20] recorded the exchange of many different substances including bacteria and concluded that there was anastomosis of capillaries that allowed large cells to exchange between animals.…”
Section: 1 Parabiosis Techniques and Limitationsmentioning
confidence: 99%
“…Starting with the initial studies by Bert [1] a number of investigators identified common blood vessels in parabiosed pairs of rats and Suaerbruch and Heyde [20] recorded the exchange of many different substances including bacteria and concluded that there was anastomosis of capillaries that allowed large cells to exchange between animals. Other investigators, however, failed to see equilibrium in the concentration of specific factors in the two members of a pair, or observed a limited physiologic response to administration of a toxin or a hormone in the partner of a treated animal [see [38]]. This led to the conclusion that there was a “parabiotic barrier” which limited transport of certain substances and it was suggested that the exchange of factors between parabiotic partners was dependent on the lymphatic system and exchange of body fluids in the common peritoneal cavity (see [2]).…”
Section: 1 Parabiosis Techniques and Limitationsmentioning
confidence: 99%
“…It is important to note that the nature of exchange between parabiotic rats is relatively slow, with total blood volume exchanging approximately ten times per day (Huff, Trautman, & Van Dyke, 1950). For a factor to reach equilibrium across the parabiotic union it has to have a half life that is longer than the rate of removal from the circulation by two animals.…”
Section: The Parabiotic Modelmentioning
confidence: 99%
“…For a factor to reach equilibrium across the parabiotic union it has to have a half life that is longer than the rate of removal from the circulation by two animals. The size of the factor is not an issue because Huff et al (Huff, Trautman, & Van Dyke, 1950) demonstrated that radiolabeled red blood cells exchanged between parabiosed rats and this has recently been confirmed using mice expressing green fluorescent protein (Gibney, et al, 2012). In 1950 Van Dyke et al (Van Dyke, Simpson, Li, & Evans, 1950) showed that growth hormone, which was estimated to have a half life of 9 hours in the circulation, reached approximately half the concentration in a hypophysectomized partner as that of the intact parabiont.…”
Section: The Parabiotic Modelmentioning
confidence: 99%